Imperialismo, dependência e o aprofundamento da degradação da Amazônia Brasileira: uma análise de 2016-2023 - Azevedo, Laís Benevenuto de (2024)
The Amazon has become an object of capital plunder since its colonial insertion process into the capitalist accumulation regime. Furthermore, the looting of its wealth, the imperialist disputes around its borders and the genocide and forced labor exploitation of traditional Amazonian peoples are part of the violent movement to consolidate capitalism as a world system. Throughout history, the faces of spoliation change, but at its root remain the search for profit, the dependent position of the Brazilian economy and the alignment between the internal, associated, transnational bourgeoisie and the State in conducting super-exploitative projects on the territory. We have observed, however, a movement of violent acceleration in the systematic plundering of Amazonian resources since 2016; so that in this research we seek to investigate the conditions for such acceleration and the possible changes in the nature of the withdrawal itself. Our hypothesis is that the Amazon becomes a space for capital appreciation at an exponentially accelerated pace, following the financialization of capitalism, representing strategic territory for the active insertion of the Brazilian economy in the financial markets. And that, from then on, the promotion of a neo-extractivist economy by the progressive governments of the first decade and a half of the 21st century, boosted the class organization movement of the bourgeoisie linked to agribusiness. Which, given the subsequent fall in profit rates, are linked to a complete neoliberal resumption of the institutional apparatus and the unrestricted advance of capital over natural borders, in a neoconservative and neofascist turn represented in the figures of Michel Temer and Jair Bolsonaro. Our analysis starts from historical-dialectical materialism as a method and uses, procedurally, the vast literature that addresses the relations of plundering of capital over labor factors in Latin America, the global movement of resurgence of Accumulation by Dispossession as an aegis of financialized capitalist accumulation and the formation of a political economy pact around Brazilian neo-extractivism, which encourages the advance of capital into the Amazon through the bourgeoisie organized in favor of its class interests.